Mobile technologies - Sørensen, Carsten (Henry Stewart Talks, 2011)
Mobile Information Technology, Mobilising Interaction, Modest Expectations, The Mobile Phone, Beyond the Mobile Phone, Three Core Mobile Capabilities, Ubiquitous Computing, Digital Convergence, Enterprise Mobility, Spaces Organising Interaction, Enterprise Mobility Around the Globe, Modalities of Mobility, Leavitt's Diamond, What is Unique About Enterprise Mobility, Creativity in Interaction, Mobile Collaboration, Control and Intervention, Enterprise Mobility Challenges, Mobile IT Matters!
Archived at 2022/04/26